Small Scale Wind Generation System: Part I – Experimental Verification Of Flux Reversal Generator Block - B. Vidhya; K. N. Srinivas (Institute of Advanced Engineering and Science, 2017)
This research work, titled Small Scale Wind Generation System, reported in part I and part II, proposes modeling, analysis and control of a small scale wind energy conversion system employing a direct driven Flux Reversal Generator (FRG) connected to the micro grid through a Quasi-Z-Source Inverter (QZSI). The application of QZSI using FRG to feed micro grid is proposed for the first time in this research work. The QZSI can realize buck/boost, inversion and power conditioning in a single stage with improved reliability. Also it features a wide range of voltage gain which is suitable for applications in wind systems, due to the fact that the wind generator output varies widely with wind velocity. In addition, the modified Space Vector PWM (SVPWM) technique is proposed in this paper to satisfy the shoot-through characteristic of QZSI. This also adds to the contribution of this research work. In this part I of this full research, modelling of the small scale FRG for wind system using Finite Element Analysis (FEA) is presented. The major parameter of FRG viz, voltage, current, torque and power are analyzed, validated and then represented in d-q model. The simulation results are validated with the analytical results. An experimental set-up to run the full procedure reported in this paper. These results form the basis for part II of this research work.